An objective method of validating pure-tone threshold - M, Raghunath (Journal of All India Institute of Speech and Hearing)
Because of the serious limitation of the pure-tone audiometry, more and more objective techniques are sought to arrive at accurate and valid thresholds. The present study is th refore an attempt to compute hearing thresholds from the stapedial reflex thresholds